2015
DOI: 10.1186/1475-925x-14-s1-s13
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and ultrasound characteristics of atherosclerosis in rhesus monkey

Abstract: Background: Atherosclerosis is one of the main risk factors cause acute cerebralcardio vascular diseases. It's of great significance to establish an atherosclerosis animal model that can mimic the characteristics and nature course of human patients. Therefore, a rhesus monkey model was induced by high-fat diet to monitor their lipid profile and intima-media thickness (IMT) of artery walls and study atherosclerosis progression. Methods: Fifty male rhesus monkeys were enrolled in this study. All of these monkeys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…Our present study proved that 1-year feeding with IPB-1 diet increases the presence of plaque (by USG), in which the prevalence of plaques in the left arteries was higher than the right arteries in both common carotid and carotid BIF. These results differ from those reported in rhesus macaques that high-fat diet-induced plaques are more worse in the right carotid arteries [32].…”
Section: Discussioncontrasting
confidence: 99%
“…Our present study proved that 1-year feeding with IPB-1 diet increases the presence of plaque (by USG), in which the prevalence of plaques in the left arteries was higher than the right arteries in both common carotid and carotid BIF. These results differ from those reported in rhesus macaques that high-fat diet-induced plaques are more worse in the right carotid arteries [32].…”
Section: Discussioncontrasting
confidence: 99%
“…FPG, 2hPPG, HbA1c and lipid parameters were measured as we previously performed [ 23 , 26 ]. Body mass index (BMI) was calculated using body weight divided by the square of CRL.…”
Section: Methodsmentioning
confidence: 99%
“…3 In addition, it was previously reported that fasting could affect the serum biochemistry profile of apparently healthy male and female cynomolgus monkeys, but its effect was not evaluated in this study. 17 The rescued LTM in this study were not…”
Section: Discussionmentioning
confidence: 64%